A SWOT analysis of the Communicative English Language Skills Improvement Programme: A Tool for Autonomous EFL Learning - Soler Pardo, Betlem; Alcantud Díaz, María (Complutense Journal of English Studies, 2020)
The digital revolution of recent years has led to new ways of learning by combining innovative and traditional methods. In order to engage the students in these new methods, a pilot project called the Communicative English Language Skills Improvement Programme (CELSIP) has been designed. Thus the learners will be able to achieve a higher level of communication in English through a wide range of multimedia resources, such as audio-books, learning apps, educational websites, TV series, films, board games, and music. These multimodal tools are of easy access to students since the vast majority are user-friendly. Hence, the main objective of this paper is to analyse and verify the feasibility of the CELSIP using a SWOT framework analysis to show the self-learning potential regarding English as a foreign language. In order to do so, we shall first describe the characteristics of the project named CELSIP. It is hoped that the SWOT analysis will provide an objective and critical perspective of the Programme’s usefulness and effectiveness as a whole. Also, this analysis could offer prompts involved in the analysis of what is effective and less effective in the programme sections and procedures.